ANALISIS PENGGUNAAN LIVE SHOPPING TIKTOK DALAM MENDORONG MINAT BELI KONSUMEN SKINTIFIC - Audy Yudistira Lenggihunusa; Evelyn Sanadi; Sam’un Jaja Raharja; Lina Auliana; Marsha Aulia Hakim (JURNAL LENTERA BISNIS, 2024)
In this study, the impact of Live Shopping on sales strategies, particularly within the skincare industry focusing on Skintific, was explored. Qualitative exploratory research involving interviews and observations of 7 consumers revealed that Live Shopping influences purchase interest through direct discounts, direct interaction with hosts, and detailed product explanations. Its influence was reflected in increased transactional, referential, preferential, and exploratory interest of consumers in Skintific products. Factors such as streamer credibility, interactivity, and the richness of media information also influenced purchase decisions. The research findings confirm that Live Shopping on TikTok is effective in influencing consumer purchase interest in skincare products such as Skintific. Keywords: Live Shopping, Purchase Interest, Digital Marketing